Associations of cerebral perfusion with infarct patterns and early neurological outcomes in symptomatic intracranial atherosclerotic stenosis - Xu, Xiangming; Lan, Linfang; Li, Zhuhao; Zhou, Wenli; Yang, Jing; Leng, Xinyi; Fan, Yuhua (Frontiers in Neurology, 2025)
ObjectivesIntracranial atherosclerotic stenosis (ICAS) is a major cause of ischemic stroke, with various infarct patterns. We aimed to investigate the cerebral perfusion features underlying different infarct patterns and the relationship between cerebral perfusion and early neurological outcomes in symptomatic ICAS (sICAS).MethodsPatients with 50%–99% sICAS in the anterior circulation were enrolled. Cerebral perfusion measures were obtained from computed tomography (CT) perfusion images, including infarct core volumes, penumbra defined with Tmax values > 6 s and > 4 s, and penumbra-core mismatch. Infarct patterns on diffusion-weighted magnetic resonance imaging (MRI) were categorized into four categories: borderzone, perforator, territorial, and mixed patterns. A favorable early neurological outcome was a decrease in the National Institutes of Health Stroke Scale (NIHSS) of ≥1 point at discharge compared with admission.ResultsWe recruited 144 patients (median age: 66 years; 61.8% male patients). Significant perfusion compromise was observed in patients with borderzone or territorial infarcts compared to those with perforator infarct patterns. Patients with a favorable early neurological outcome exhibited smaller volumes of penumbra and penumbra-core mismatch at baseline. A multivariate logistic regression analysis revealed that penumbra (defined by Tmax of >4 s)-core mismatch volume of >15 mL was independently associated with a lower chance of achieving a favorable early neurological outcome (adjusted odds ratio, 0.323; 95% confidence interval, 0.121–0.866; p = 0.03).ConclusionHemodynamic compromise likely underlies borderzone and territorial cortical/subcortical infarcts in patients with sICAS. The penumbra-infarct core mismatch volume in CT perfusion, with Tmax of >4 s defining the penumbra, was associated with early neurological outcomes of sICAS patients.